1997
DOI: 10.1021/es960293p
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Phenomena during Thermal Decontamination of Soils

Abstract: Effects of thermal treatment conditions on removal of a low volatility aromatic contaminant from soil are quantified. Shallow beds (10 mg) of a clay soil pretreated with 8 ( 0.4 wt % pyrene were heated in a thermogravimetric analysis at 5, 25, or 50 °C/min or isothermally. Effects of temperature, time, initial soil mass, initial contaminant mass, heating rate, and flow rate of carrier gas (helium at standard conditions) were studied, as were weight loss of uncontaminated soil and evaporation rates of pure pyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…Assuming the difference in weight loss method is valid, Figure 13 suggests that there is little effect of heating rate on pyrene removal at a peak temperature of 550°C, when heating rate was reduced from 5000 to 1000°C/sec or further from 1000 to 100°C/sec ( Figure 13). However, at somewhat lower temperatures and considerably lower heating rates, Gilot et al (27) found that a 10-fold reduction in heating rate, i.e., from 50 to 5°C/min, lowered the temperature to achieve 85% pyrene removal from a clay soil, from 275 to 200°C. Further mathematical modeling of heating rate and temperature effects on soil thermal decontamination, for broad ranges of these two variables, would shed further light on these observations.…”
Section: Effects Ofheating Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Assuming the difference in weight loss method is valid, Figure 13 suggests that there is little effect of heating rate on pyrene removal at a peak temperature of 550°C, when heating rate was reduced from 5000 to 1000°C/sec or further from 1000 to 100°C/sec ( Figure 13). However, at somewhat lower temperatures and considerably lower heating rates, Gilot et al (27) found that a 10-fold reduction in heating rate, i.e., from 50 to 5°C/min, lowered the temperature to achieve 85% pyrene removal from a clay soil, from 275 to 200°C. Further mathematical modeling of heating rate and temperature effects on soil thermal decontamination, for broad ranges of these two variables, would shed further light on these observations.…”
Section: Effects Ofheating Ratementioning
confidence: 99%
“…Differences in soil type, heating apparatus, and soil bed configuration may also be important, i.e., Gilot et al. (27) heated a shallow bed of soil in a thermogravimetric analyzer.…”
Section: Effects Ofheating Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Giot et al (10) used a thermogravimetric analyzer (TGA; Cahn System 113, Cahn Instruments, Madison, WI) to study pyrene removal (inferred from weight loss data) during much slower heating (5-50°CImin) of shallow beds of clay particles contaminated with approximately 8 wt% (by weight) pyrene. They found that rates of pyrene release from the soil bed were approximately 5-fold lower than those from heating pure pyrene under similar conditions.…”
mentioning
confidence: 99%
“…Rates [8][9][10] hr in a specially treated, inverted wide-mouth jar (8). The resulting residue, that is, the contaminated soil, was then redried in the desiccator before use.…”
mentioning
confidence: 99%